Effect Of Counterpressure With Birth Ball On Reduction Of Labor Pain In First Stage - Wira Ekdeni Aifa; Fajar Sari Tanberika; Sumandar (Institute of Computer Science (IOCS), 2022)
The use of a birth ball during labor can reduce pain levels because it stimulates postural reflexes and keeps the muscles and spine in good condition, thereby reducing anxiety, minimal use of pethidine, facilitates descent of the fetal head, reduces the length of the first stage. The purpose of the study was to determine the effect of counterpressure with birth balls on reducing labor pain in the 1st stage of labor. Types of quantitative research and pre-experimental design. The sample were 16 mothers and the sampling technique was Accidental Sampling. The research instrument was observation sheet with univariate and bivariate analysis. Data analysis used paired sample t test. The results showed that there was an effect of counterpressure with birth balls on reducing labor pain in the 1st stage, with p-value 0.000 <0.05, while the results of the different test with independent t-test obtained p-value = 0.006, which means that there was a difference between the groups that were treated with counterpressure. Birth Ball and what not to do on the reduction of labor pain in the 1st stage. It is hoped that the Sinta Medika Clinic can be an innovation for health services, especially in the field of maternity care to reduce maternal pain in the first stage